ONECUT1 variants beyond type 1 and type 2 diabetes: exploring clinical diversity and epigenetic associations in Arab cohorts - Dashti, Mohammed; Nizam, Rasheeba; John, Sumi Elsa; Melhem, Motasem; Channanath, Arshad; Alkandari, Hessa; Thanaraj, Thangavel Alphonse; Al-Mulla, Fahd (Frontiers in Genetics, 2023)
ONECUT1 gene, encoding hepatocyte nuclear factor 6, is involved in pancreas and liver development. ONECUT1 mutations impair the function of pancreatic -cells and control a transcriptional/epigenetic machinery regulating endocrine development. Homozygous nonsense and missense mutations at ONECUT1_p.E231 and a homozygous frameshift mutation at ONECUT1_p.M289 were reported in neonatal diabetes individuals of French, Turkish, and Indian ethnicity, respectively. Additionally, heterozygous variants were observed in Northern European T2D patients, and Italian patients with neonatal diabetes and early-/late-onset T2D. Examining diverse populations, such as Arabs known for consanguinity, can generalize the ONECUT1 involvement in diabetes. Upon screening the cohorts of Kuwaiti T1D and MODY families, and of Kuwaiti and Qatari T2D individuals, we observed two homozygous variants - the deleterious missense rs202151356_p.H33Q in one MODY, one T1D, and two T2D individuals, and the synonymous rs61735385_p.P94P in two T2D individuals. Heterozygous variants were also observed. Examination of GTEx, NephQTL, mQTLdb and HaploReg highlighted the rs61735385_p.P94P variant as eQTL influencing the tissue-specific expression of ONECUT1, as mQTL influencing methylation at CpG sites in and around ONECUT1 with the nearest site at 677-bases 3’ to rs61735385_p.P94P; as overlapping predicted binding sites for NF-kappaB and EBF on ONECUT1. DNA methylation profiles of peripheral blood from 19 MODY-X patients versus 8 healthy individuals revealed significant hypomethylation at two CpG sites - one located 617-bases 3’ to the p.P94P variant and 8102 bases away from transcription start; and the other located 14999 bases away from transcription start. Our study generalizes the association of ONECUT1 with clinical diversity in diabetes.